The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1038/s41467-021-25832-9
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-scale imaging of CH3NH3PbI3 structure and its decomposition pathway

Abstract: Understanding the atomic structure and structural instability of organic-inorganic hybrid perovskites is the key to appreciate their remarkable photoelectric properties and understand failure mechanism. Here, using low-dose imaging technique by direct-detection electron-counting camera in a transmission electron microscope, we investigate the atomic structure and decomposition pathway of CH3NH3PbI3 (MAPbI3) at the atomic scale. We successfully image the atomic structure of perovskite in real space under ultra-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 67 publications
(88 reference statements)
1
31
1
4
Order By: Relevance
“…[11,14] Rothmann et al used transmission electron microscopy (TEM) to quantify structural changes in methylammonium lead iodide films (MAPbI 3 ) at fluences as low as 100 e -Å -2 , [11] in which loss of the organic moieties results in lattice contraction and the formation of a supercell, further described by Chen et al as MAPbI 2.5 , ultimately degrading into PbI 2 . [15,16] The appearance of an intermediate phase of degradation agrees with similar studies by scanning electron microscopy techniques. [17][18][19] Alberti et al also reported the detrimental effect of having excess Pb-related defects during fabrication, which aggregate and feed degradation at grain boundaries upon electron irradiation.…”
supporting
confidence: 85%
“…[11,14] Rothmann et al used transmission electron microscopy (TEM) to quantify structural changes in methylammonium lead iodide films (MAPbI 3 ) at fluences as low as 100 e -Å -2 , [11] in which loss of the organic moieties results in lattice contraction and the formation of a supercell, further described by Chen et al as MAPbI 2.5 , ultimately degrading into PbI 2 . [15,16] The appearance of an intermediate phase of degradation agrees with similar studies by scanning electron microscopy techniques. [17][18][19] Alberti et al also reported the detrimental effect of having excess Pb-related defects during fabrication, which aggregate and feed degradation at grain boundaries upon electron irradiation.…”
supporting
confidence: 85%
“…Some of the impressive ones include the aforementioned in situ PL, and the electrical biasing of thin samples in situ in TEM, which has been reported to provide insight into biasinduced degradation mechanisms of MAPbI 3 PSCs at the nanoscale. [137][138][139] However, the beam sensitivity problem should be solved. In addition, more models that can simulate the dynamic equilibrium of ion migration are needed.…”
Section: Discussionmentioning
confidence: 99%
“…[ 28,29 ] Unfortunately, the applications of organic–inorganic perovskites‐based RRAM devices are limited by the poor thermal stability and moisture sensitivity, because of the instability of the organic cations and severe ion migration. [ 30,31 ] In contrast, all‐inorganic perovskite quantum dots (QDs) [ 32,33 ] or films show superior stability and reproducibility by replacing the organic cation (MA or FA) with an inorganic one (such as Cs). Thus, all‐inorganic perovskite QDs are considered to be promising candidates for use as insulating materials in RRAM devices.…”
Section: Introductionmentioning
confidence: 99%